Fondaco dei Tedeschi luxury mall - Goetzmann, William N., (SAGE Knowledge. Cases., 2017)
The renovation of the Fondaco dei Tedeschi in Venice represented a grand experiment. Should an ancient building in the midst of a world heritage site be transformed into a modern mall for luxury goods? How best to achieve the transformation and make it economically sustainable? In the 2000s, the Poste Italiane decided to move out. The Benetton family saw an opportunity. The Benettons brought on OMA to renovate the building. The Dutch architectural firm, headed by Pritzker-winner Rem Koolhaas, had to transform a centuries-old building into a modern showcase for high-end goods. They also needed to incorporate private retail into a space in which the public would feel welcome. The Benetton group then contracted with DFS to operate the mall. DFS brought an intimate knowledge of the tourist trade, but could this help them stock the mall with the proper mix of goods? Would tourists walk to the mall? And would they buy or just look? Would the mall become economically viable? What could each stakeholder learn from their experiences with the Fondaco dei Tedeschi?